Long-Term Muscarinic Inhibition Increases Intrinsic Excitability Through the Upregulation of A-Type Potassium Currents in Cortical Neurons - Leiva-Salcedo, D; Riquelme-Pacheco, D; Moreno-Pohl, C (Frontiers Media SA, 2025)
Neurons undergo a series of perturbations that alter their firing rate and synaptic transmission; however, they can adapt to keep a target level of electrical activity in the long term. Muscarinic receptor (mAChR) transmission modulates intrinsic excitability and allows for fast changes through phasic transmission and long-term effects through volume transmission. Earlier studies on mAChR transmission have primarily focused on the effects of long-term mAChR stimulation on excitability; however, the impact of long-term inhibition is still unknown. In this study, we used a combination of patch-clamp and immunofluorescence techniques to examine the effects short-term (3 h) and long-term (0–10 days) muscarinic or nicotinic (nAChR) receptor inhibition on the intrinsic excitability of cortical pyramidal neurons in culture. We found that short term mAChR or nAChR inhibition has no effect either in AIS or in neuronal excitability, however, prolonged mAChR, but not nAChR blockade, increases the AIS length with no change in its position. Moreover, prolonged mAChR blockade increases firing frequency and intrinsic excitability, through a reduction in the action potential duration that is the result of an increase in a 4-AP sensitivity K+ current in cortical pyramidal neurons in culture. Together, our work demonstrates that prolonged mAChR, but not nAChR, blockade induces structural and functional changes to compensate for the lack of mAChR signaling and to sustain a target level of electrical activity. © © 2025 Riquelme, Romo-Toledo, Leyton, Moreno and Leiva-Salcedo.